Implementasi Pembelajaran Tatap Muka Terbatas Pendidikan Pancasila dan Kewarganegaraan Dimasa Pandemi Covid-19 - Sukmawati, Sukmawati; Anita, Anita; Jamaluddin, Jamaluddin; Hanis, Hasdin (Jurnal Kewarganegaraan, 2023)
AbstractThis study aims to describe the implementation of limited face-to-face learning during the Covid-19 pandemic, as well as describe how the solutions to stunned the Covid-19 Pandemic at One Roof 1 Ampibabo Public Middle School, using qualitative research methods with descriptive research types. The results of the study (1) the implementation of limited face-to-face learning in the learning process during the Covid-19 pandemic was shifts to school, besides studying at school the teacher also used WhatsApp social media, only 15 minutes of rest time, 20 students in class, the distance between students sitting with each other complies with health protocols. The lack of parental assistance during learning causes students to be less disciplined, and students complain about assignments that are piling up. (2) The solution to overcome the implementation of limited face-to-face learning is that the school implements class shifts so that students do not come to school too much because there are restrictions on students in class so as to reduce the risk of Covid-19 symptoms.------------AbstrakPenelitian ini bertujuan mendeskripsikan implementasi pembelajaran tatap muka terbatas dimasa pandemi Covid-19, serta mendeskripsikan bagaimana solusi dalam mengatasi dimasa Pandemi Covid-19 di SMP Negeri Satu Atap 1 Ampibabo, dengan menggunakan metode penelitian kualitatif dengan tipe penelitian deskriptif. Hasil penelitian (1) pelaksanaan pembelajaran tatap muka terbatas dalam proses pembelajaran selama masa pandemi Covid-19 adalah sift masuk sekolah, selain belajar di sekolah guru juga memanfaatkan media sosial whatsapp, waktu istirahat hanya 15 menit, siswa yang berada di dalam kelas berjumlah 20 orang, Jarak duduk antara siswa satu dengan yang lain sudah mematuhi protokol kesehatan. Kurangnya dampingan orang tua pada saat pembelajaran menyebabkan siswa kurang disiplin, keluhan siswa mengenai tugas yang sangat menumpuk. (2) Solusi untuk mengatasi implementasi pembelajaran tatap muka terbatas yaitu pihak sekolah menerapkan sift kelas agar siswa tidak terlalu banyak datang kesekolah karena ada pembatasan siswa dalam kelas sehingga dapat mengurangi resiko terjadinya gejala Covid-19.